The William Blake Archive - Crawford, Kendal,Levy, Michelle (Enthalten in:RIDE;Köln : Institut für Dokumentologie und Editorik, [2014]-;Online-Ressource)
Abstract: The William Blake Archive (WBA) attempts to remediate digitally William Blake’s entire corpus of poetic and artistic artifacts. The resulting website exhibits high-fidelity images of his surviving prints, plates, drawings, and canvases that would otherwise remain isolated in difficult-to-access collections around the world. Using an editorial strategy that focuses on the physical object, the WBA successfully individuates physical copies of Blake’s work by supplementing each digital facsimile with unique bibliographic information, editorial commentary, and viewing tools that help users investigate the object’s unique material nature. Functionally, the site would greatly benefit from updates to its user interface and key applet (the Virtual Light Box). The project succeeds as a scholarly digital edition by providing curated and contextualized access to Blake’s literary and artistic output, implementing its core editorial strategy since the archive was launched twenty years ago, in ...
10.18716/ride.a.5.5
Keywords: 19th century; annotation; archive; Blake; collation; collected works; comparative edition; critical digitization; critical edition; diplomatic transcription; english; facsimile; iconography; illustration description; illustrations; image search; indices; interactive edition; materiality; multi-generic; romantic; TEI; virtual workspace